PENGARUH TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR SISWA SMAS AL HUDA KECAMATAN TAMPAN KOTA PEKANBARU - Siti Irliansyah Nasution; Ahmad Eddison; Indra Primahardani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by the existence of groups of friends at school. This will cause students to spend more time with their friends, of course this will create the same perception among students about learning, it is undeniable that students about will equal their group of friends in all respects if good peers will be good also a students and vice versa. If students have peers who have low levels of motivation, students who have relationships with their peers will certainly have the same behavior and follow suit. The problem formulation of this research is how the influence of peers on the learning motivation of students SMAS Al Huda. The purpose of this study was to find out how the influence of peers on students motivation at SMAS Al Huda Tampan District Pekanbaru City. Practical benefits for researchers is to increase knowledge, insigt and understanding of the factors that can affect student learning motivation, then it can be applied when the author becomes a teacher or parent. The population of this study were all students of SMAS Al Huda totaling 229 students. The sample in this study was 57 people with the sampling technique used, namely proportional random sampling, then random sampling. Data collection methods are questionnaires, observations, interview and documentation. Data processing with quantitative descriptive analysis using a simple linear regression formula assisted by the SPSS version 23 application. Based on the results of research on the influence of peers on the learning motivation In students of SMAS Al Huda Tampan District Pekanbaru City, it can be concluded that there is an influence of peers on the learning motivation in students of SMAS Al Huda Tampan District Pekanbaru City which is 26,1%.Key Words: Influence, Peers, Learning Motivation